1993
DOI: 10.1182/blood.v81.1.9.9
|View full text |Cite
|
Sign up to set email alerts
|

F reticulocyte response in sickle cell anemia treated with recombinant human erythropoietin: a double-blind study

Abstract: Studies on baboons and preliminary observations in three patients with sickle cell anemia (SS) suggested that high doses of pulse administered recombinant human erythropoietin (rHuEPO) stimulate F-reticulocyte production. We now report on the administration of rHuEPO in a double- blind format to ascertain frequency of response and potential precipitation of side effects. Ten patients were enrolled, but one was discontinued due to the indication of a blood transfusion. Of the other nine, five received rHuEPO in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…In patients who develop renal failure, higher doses of ESA, ranging from 150 to 250 u/kg/d, may be necessary and appear to be well tolerated (Roger et al, 1991;Steinberg, 1991;Tomson et al, 1992). In a randomized trial utilizing ESA doses up to 800 u/kg/d (Nagel et al, 1993) in patients with renal failure, no side effects were observed. Similarly high doses have been used effectively in SCD cases with life-threatening DHTR (Little et al, 2006).…”
Section: Directed Treatmentsmentioning
confidence: 99%
“…In patients who develop renal failure, higher doses of ESA, ranging from 150 to 250 u/kg/d, may be necessary and appear to be well tolerated (Roger et al, 1991;Steinberg, 1991;Tomson et al, 1992). In a randomized trial utilizing ESA doses up to 800 u/kg/d (Nagel et al, 1993) in patients with renal failure, no side effects were observed. Similarly high doses have been used effectively in SCD cases with life-threatening DHTR (Little et al, 2006).…”
Section: Directed Treatmentsmentioning
confidence: 99%
“…Immature and larger reticulocytes are released from bone marrow during erythroid expansion in response to hemolysis. These reticulocytes coexpress adult and fetal globin (F-reticulocytes) (5,6). SCD patients receiving HU showed a decrease in the number of immature reticulocytes and in cell density, but there was no statistically significant increase in percent HbF or absolute HbF levels (7).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore there may be a rationale for r-HuEpo treatment in haemolytic anaemias, if the anaemia does not achieve an optimal Epo drive. On this basis it has been experimented with in, for instance, sickle cell anaemia (Nagel et al, 1993). In order to assess whether this rationale might be applicable to PNH, a condition in which r-HuEpo has been also used empirically, we thought it was necessary to first determine the levels of endogenous Epo.…”
Section: Discussionmentioning
confidence: 99%